SURVEY OF PLANT-PARASITIC NEMATODES ASSOCIATED WITH CASSAVA IN OSUN STATE, NIGERIA - SANGOYOMI, T. E.; AMULU , L. U.; ADEKUNLE, O. K. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A survey was conducted to determine the types, frequency and population of plant parasitic nematodes associated with cassava (Manihot spp.) in three agro-ecological regions of Osun state of Nigeria. The state was divided into three agricultural zones which included; Iwo, Oshogbo and Ife/Ijesha. The survey was conducted in October 2010 and November 2012. In each zone, 20 cassava-based farms were randomly selected for sampling. In each farm, 30 plants were randomly sampled. Soil samples were collected around the roots of each plant using a soil auger and plant parasitic nematodes were extracted from the soil samples. Identification of plant parasitic nematodes to the generic level was carried out. Five genera of plant parasitic nematodes were encountered in soil samples collected from the three zones including Meloidogyne spp., Pratylenchus spp., Helicotylenchus spp., Scutellonema spp., and Paratylenchus spp. Apart from Paratylenchus spp. these nematodes have been implicated worldwide as important nematode pests of cassava. Meloidogyne spp. was the most frequently occurring species in the State followed by Pratylenchus, Helicotylenchus and Scutellonema spp. The least occurring species was Paratylenchus. These plant-parasitic nematodes could constitute a problem to cassava production in Osun State.